Design Optimization of a Heat Thermal Storage Coupled with a Micro-CHP for a Residential Case Study. (November 2016) - Magnani, Sandro; Pezzola, Lorenzo; Danti, Piero
Abstract: Energy efficiency is a key target of the European Union policy. The "Europe 2020 strategy" quantitative targets account an increase by 20% of the energy efficiency by the end of 2020. The attention to power sources optimization and energy waste reduction leads European Countries to develop subsidy strategies to drive the energy market towards efficiency enhancement. According to this trend, energy efficiency of residential buildings has significantly grown in Italy in the last years. Combined production of electric and thermal power is a notable example of efficiency enhancement awarded by the CAR ( Cogenerazione ad Alto Rendimento ) Italian subsidies system. In these circumstances, the optimization of the ensemble between power generators and thermal storages becomes crucial to satisfy in an efficient way thermal power requirement independently from electric power production. The purpose of this paper is to find the optimal power plant design of power generators and thermal storages in order to minimize daily management costs and environmental impact. The power plant layout in analysis consists in a micro-CHP (Combined Heat and Power) and an absorption chiller both coupled with respective thermal storages. Through this evaluation, it is possible to identify the optimal coupling of the devices as a function of the load requirements and understand the great influence of their sizing on the energy management benefits. The analysis is performed with reference to cold and warm thermal load required by a residential case study. The performance analysis takes place in representative days of different seasons and the results are extended on an annual base. The power request profiles are developed on the basis of literature data. The results are compared on an economic basis considering the NPV (Net Present Value) index, evaluated using as the benchmark a standard plant layout composed by a water boiler and an electric chiller.